Follow-up of breast cancer patients: Preliminary findings from nurse-patient consultations and patient surveys - Jiwa, M.; Halkett, Georgia; Deas, K.; O Connor, M.; Weir, J.; O Driscoll, C.; O Brien, E.; Wilson, L.; Boyle, S. (Australasian Medical Journal Pty Ltd, 2009)
© 2014, Australasian Medical Journal. All rights reserved.Background: Although clinicians in both primary and tertiary care settings are involved in the care of breast cancer patients following the active treatment phase, few studies report how patients interact with health care providers.Methods: Participants in this breast cancer follow-up study were recruited from a hospital based nurse-led follow-up clinic in Western Australia. Methods included audio taped, transcribed consultations with Specialist Breast Nurses (SBNs) and patient self-completed surveys.Results: Preliminary data suggest that SBNs play an important role in supporting women to deal with the impact of breast cancer in the years following active treatment. The data suggest that the process of adjustment to a diagnosis of cancer continues for many years after the treatment has ceased. In many cases the women require on-going support to recalibrate their response to normal physical changes that may or may not be a consequence of surgery, radiotherapy and chemotherapy.Conclusions: These preliminary data map the plethora of issues that influence cancer patients in the years following treatment. Women who were attending follow-up appointments for breast cancer experienced similar levels of enablement following SBN consultations as would be expected from consultations with general practitioners.